TLR4-mediated brain inflammation halts neurogenesis: impact of hormonal replacement therapy - Mouihate, Abdeslam (Frontiers in Cellular Neuroscience, 2014)
Experimental and epidemiological data show that the severity and the duration of brain inflammation are attenuated in females compared to males. This attenuated brain inflammation is ascribed to 17β-estradiol. However, several studies suggest that 17β-estradiol is also endowed with proinflammatory properties. The aim of the present study is to assess the effect of hormonal replacement therapies on LPS-induced brain inflammation and its consequent effect on newly born neurons. Bilaterally ovariectomized rats received intrastriatal injection of lipopolysaccharide (LPS, 250 ng/µl) and subsequently were given daily subcutaneous injections of either vehicle, 17β-estradiol (25 µg/kg) or 17β-estradiol and progesterone (5mg/kg). Microglial activation and newly-born neurons in the rostral migratory stream were monitored using double immunofluorescence. Nuclear factor κB (NFκB) signaling pathway and its target inflammatory proteins were assessed by either western blot (cyclooxygenase-2 (COX-2) and interleukin-6 (IL-6)) or ELISA (Tumor Necrosis Factor-α (TNFα)). LPS induced activation of microglia, promoted NFκB signaling pathway and enhanced production of the pro-inflammatory proteins (TNFα and COX-2). These proinflammatory responses were not attenuated by 17β-estradiol-injection. Supplementation of 17β-estradiol with progesterone significantly dampened these pro-inflammatory processes. Interestingly, LPS-induced brain inflammation dampened the number of newly born neuron in the rostral migratory stream. Administration of combined 17β-estradiol and progesterone resulted in a significantly higher number of newly born neurons when compared to those seen in rats given either vehicle or 17β-estradiol alone. These data strongly suggest that combined 17β-estradiol and progesterone, and not 17β-estradiol alone, rescues neurogenesis from the deleterious effect of brain inflammation likely via the inhibition of the signaling pathways leading to the pro-inflammatory gene activation.